Differences in HIV knowledge and sexual practices of learners with intellectual disabilities and non‐disabled learners in Nigeria. Issue 1 (8th February 2013) - Aderemi, Toyin J; Pillay, Basil J; Esterhuizen, Tonya M
Abstract : Introduction: Individuals with intellectual disabilities are rarely targeted by the current human immunodeficiency virus (HIV) response, thereby reducing their access to HIV information and services. Currently, little is known about the HIV knowledge and sexual practices of young Nigerians with intellectual disabilities. Thus, this study sought to compare the HIV knowledge and sexual practices of learners with mild/moderate intellectual disabilities and non‐disabled learners (NDL) in Nigeria. Findings could help in the development of HIV interventions that are accessible to Nigerian learners with intellectual impairments. Methods: This cross‐sectional, comparative study utilized a survey to investigate HIV knowledge and sexual practices among learners with mild/moderate intellectual disabilities and NDL in Nigeria. Learners with mild/moderate intellectual disabilities ( n= 300) and NDL ( n= 300) within the age range of 12 to 19 years drawn from schools across Oyo State, Nigeria, completed a structured questionnaire to assess their knowledge of HIV transmission and sexual practices. Results: Significantly more learners with mild/moderate intellectual disabilities (62.2%) than NDL 48 (37.8%) reported having sexual experience ( p =0.002). Of the sexually experienced female learners with mild/moderate intellectual disabilities, 28 (68.3%) reported history of rape compared with 9 (2.9%) of female NDL ( p =0.053). Intellectual impairment was significantly associated with lower HIV transmission knowledge scores ( p <0.001). Learners with mild/moderate intellectual disabilities were less likely than NDL ( p <0.001) to have heard about HIV from most of the common sources of HIV information. In addition, when compared with non‐disabled learners, learners with mild/moderate intellectual disabilities were significantly more likely to have reported inconsistent condom use with boyfriends/girlfriends ( p <0.001), with casual sexual partners ( p <0.001) and non‐use of condom during last sexual activity ( p <0.001). Conclusions: Findings suggest that adolescents with intellectual impairments are at higher risk of HIV infection than their non‐disabled peers. This gap could be addressed through interventions that target Nigerians with intellectual impairments with accessible HIV information and services.